The launching of green impact initiatives - College of Liberal Arts - De La Salle University, Manila (Animo Repository, 2021)
The De La Salle University College of Liberal Arts (CLA) invited the academic community to THE LAUNCHING OF GREEN IMPACT INITIATIVES on 3 December 2021, Friday, 10AM-12NN via Zoom.